The state of the notion knowledge management in practice - Ruggles, Rudy (California management review)
To a growing number of companies, knowledge management is more than just a buzzword or a sales pitch, it is an approach to adding or creating value by more actively leveraging the know-how, experience, and judgement resident within and, in many cases, outside of an organization. Based primarily upon the results of a study of 431 U.S. and European organizations, this article describes what firms are actually doing to manage knowledge, what else they think they could be or should be doing, and what they feel are the greatest barriers the face in their efforts.